PWE-197 Is MRCP a useful Investigation where the Biliary Tree is normal on Previous Imaging?. (4th June 2013) - Vadhwana, B; Graby, J; Yusuf, A; Sergot, A; Ramsey, C; Monahan, K
Abstract : Introduction: Magnetic Resonance Cholangiopancreatography (MRCP) is increasingly used in the diagnosis of biliary disease, especially in stone disease. It has a high sensitivity and specificity[1] [2]; however its role in the absence of dilated biliary tree on previous imaging is not clear. The aim of this study was to determine the diagnostic yield of MRCP in patients with an undilated biliary tree. Methods: We performed a retrospective observational study of MRCP studies (n = 119) performed between October 2011 and September 2012 at West Middlesex University Hospital using electronic medical records. All MRCPs were reported by a consultant radiologist. MRCP findings were correlated with the presence of dilated (but otherwise normal) or undilated biliary tree on initial imaging (USS/CT), jaundice (bilirubin > 21 μmol/L) and abdominal pain. Demographics including age and gender were noted. Fisher's exact test was used to analyse binary variables and student's T test for continuous variables using the STATA12 statistical software Results: In patients with a normal biliary tree on previous imaging the yield of MRCP was low with only 2/44 demonstrating stone or other pathology (p = 0.0002). Patient referred for MRCP without biliary tree dilatation had a median age 12 years younger (p = 0.033) and the indication was more likely to be pain (p = 0.017) but not jaundice (p = 1) and referrals were not gender related (p = 0.23). Conclusion: Our study demonstrates a low diagnostic yield of MRCP in the absence of dilated biliary system on previous USS/CT. Furthermore, the presence of jaundice or abdominal pain does not help to select patients who may benefit from further biliary imaging with MRCP. Routine MRCP in patients with an undilated biliary tree on USS/CT does not appear to be indicated. Disclosure of Interest: None Declared. Reference: ShanmugamV, Beattie GC, Yule SR, et al. Is magnetic resonance cholangiopancreatography the new gold standard in biliary imaging? British Journal of Radiolog y (2005) 78, 888–893. Williams EJ, Green J, Bechingham I, et al. Guidelines on the management of common bile ductstones (CBDS). Gut 2008; 57:1004–1021.